2016
DOI: 10.1007/s00163-016-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of information and communication technologies on creativity in collaborative design

Abstract: This study compares the degree of creativity of forty-two conceptual designs proposed as solutions to two innovative design problems developed in face-to-face and virtual collaborative environments. The solutions obtained were evaluated by three experts applying the Moss metric, which considers the level of usefulness and the level of unusualness. The average values and the trends of the data were obtained and an analysis of the variance was also performed to determine whether the environment influences the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…However, this difference does not seem to have any direct influence on creativity, nor on productivity in particular. This corresponds with the work of Tang et al (2011) andChulvi et al (2017), who found that digital setups did not significantly influence measurable creativity in sketching.…”
Section: Differences Between Digital and Physical Notessupporting
confidence: 86%
See 1 more Smart Citation
“…However, this difference does not seem to have any direct influence on creativity, nor on productivity in particular. This corresponds with the work of Tang et al (2011) andChulvi et al (2017), who found that digital setups did not significantly influence measurable creativity in sketching.…”
Section: Differences Between Digital and Physical Notessupporting
confidence: 86%
“…In relation to turn-taking, we further look at how the digital versus physical material affects alternation between individual and group idea generation, as mentioned by Korde and Paulus (2017). Our work is also influenced by Tang et al (2011) and Chulvi et al (2017), who investigate how moving from a physical to a digital setup influences creativity in different sketching environments, and by work on artefact mediation, and affordances for interaction at large (Baerentsen and Trettvik 2002, Gaver 1992, Badram and Houben 2018.…”
Section: Related Workmentioning
confidence: 99%
“…So, together with the defended hypothesis that knowledge co-generation can enhance design creativity, this fact can also reinforce previous studies that point that teamwork increase novelty and creativity (Alves et al, 2007;González-Cruz et al, 2008). Also, previous studies demonstrated that the use or not of ICTs doesn't affect the level of creativity of the results (Chulvi et al, 2016), so this is a factor that we can discard on our research.…”
Section: Discussionmentioning
confidence: 91%
“…Fully-synchronous CAD software provides an appealing instrument with which to explore these factors. An example future study of interest would investigate the creativity of the product enabled by fully-synchronous collaborative design teams when compared to results already discovered for creativity with traditional CAD use and other virtual tools (Chulvi et al, 2017;Häggman et al, 2015;Robertson and Radcliffe, 2009). Another might be a study of team composition, specific to the CAD context and compared to previous findings on collaborative design (McComb et al, 2016).…”
Section: Future Workmentioning
confidence: 97%